Antibody response after two doses of the SARS-CoV-2 Comirnaty vaccine in a Covid-19 positive and Covid-19 negative Italian healthcare workers cohort. (1st April 2022) - Sulejmani, Adela; Giacobone, Chiara; Spiti, Simona; Pozzobon, Claudia; Dominici, Roberto; Mascagni, Paolo; Falbo, Rosanna; Brambilla, Paolo; Leoni, Valerio
Abstract: Background: Extensive vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is now universally regarded as one of the most effective strategies for counteracting the current pandemic. The durability of the immune response of available vaccines is not known, therefore the quantitative dynamics of serum anti-S antibodies after Comirnaty vaccine in health care workers (HCW) of Desio Hospital was conducted. Methods: 51 previously infected and 198 not infected HCW, from Desio, Italy were enrolled in the study. Comirnaty double dose schedule was completed by each subject. Specific anti-S antibodies against the SARS-CoV-2 S protein were measured by ECLIA in sequential blood samples. Results: A significant difference was observed beginning at pre priming dose (T0) of the anti-S antibodies between the two subgroups which persisted throughout the study (4 months). A significant reduction occurred after 4 months post-priming dose (T3). Finally, a subgroup of low and late responders with an increasing trend was found. Conclusions: Specific anti-S antibodies are significantly decreased 4 months post priming dose of Comirnaty vaccine although prior COVID-19 infection seems to escalate humoral response. Further evaluation concerning antibody persistence beyond this point, and the proportion of neutralizing antibodies with higher affinity towards SARS-CoV-2 is needed, especially in naїve and immunosuppressed subjects.